2015
DOI: 10.3233/jad-150033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Training on Cognition and Brain Glucose Metabolism in Subjects with Mild Cognitive Impairment

Abstract: AT improved cognition and changed rBGM in areas related to cognition in subjects with MCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 64 publications
2
17
1
Order By: Relevance
“…Results from this pilot study support growing evidence that shows physical activity or exercise benefits cognitive function in older adults with MCI. 13 17 , 37 The finding on the improved ADAS-Cog scores is consistent with previous exercise-based interventions involving home-based aerobic 13 and multimodal exercises. 14 To the best of our knowledge, this is the first time that a momentum-based dumbbell-training approach has been used to target change in cognition function.…”
Section: Discussionsupporting
confidence: 88%
“…Results from this pilot study support growing evidence that shows physical activity or exercise benefits cognitive function in older adults with MCI. 13 17 , 37 The finding on the improved ADAS-Cog scores is consistent with previous exercise-based interventions involving home-based aerobic 13 and multimodal exercises. 14 To the best of our knowledge, this is the first time that a momentum-based dumbbell-training approach has been used to target change in cognition function.…”
Section: Discussionsupporting
confidence: 88%
“…While others have reported that acute aerobic exercise [46] and aerobic training interventions [47] can alter cerebral glucose metabolism, our findings suggest that engagement in MPA, specifically, may promote cerebral glucose metabolism among cognitively normal late-middle-aged adults at risk for AD. While we cannot draw definitive conclusions regarding causation in this study, our findings, in the context of the literature suggest PA tracks closely with cerebral glucose metabolism.…”
Section: Discussioncontrasting
confidence: 63%
“…Our findings are in accordance with a previous study demonstrating that aerobic exercise training may benefit brain glucose metabolism. Porto and colleagues reported that 24 weeks of aerobic exercise training increased PCC glucose metabolism among individuals with MCI [47]. Their exercise training was similar in session duration, intensity, and intervention duration, but was lower in total training volume (i.e., two sessions/week) and the improvement in CRF was approximately half of that observed in our Enhanced PA group.…”
Section: Discussionmentioning
confidence: 59%